Highly efficient and stable carbon-based perovskite solar cells with the polymer hole transport layer. (15th May 2021) - Jin, Junjun; Yang, Man; Deng, Wenqiu; Xin, Juan; Tai, Qidong; Qian, Jingwen; Dong, Binghai; Li, Wenlu; Wang, Jianying; Li, Jinhua
Graphical abstract: Highlights: Carbon-based perovskite solar cells are prepared at fully low temperature. P3HT is employed as the hole transport layer at the C-PSCs. The high power conversion efficiency of 16.05% is achieved. The PCE retains over 90% of its initial value after storing for 1200 h. Abstract: Carbon-based perovskite solar cells are competitive candidate for photovoltaic applications in future due to their high-performance, low-cost and good stability. However, the hole transport materials are limited and their properties are not satisfying in carbon-based perovskite solar cells. Here, we report a typical p-type P3HT as hole transport layer for all low-temperature processed carbon-based perovskite solar cells with ZnO electron transport layer. Because P3HT has energy level matching with perovskite film and can facilitate the hole collection process, the power conversion efficiency of device can reach 16.05% that far higher than devices without P3HT hole transport layer. More importantly, due to good hydrophobicity and encapsulation function of P3HT, the stability of devices can also be significantly improved. The power conversion efficiency of device is able to retain over 90% of their initial value over 1200 h upon ambient air exposure without encapsulation. This present study provides a simple strategy for fabricating low-cost, highly efficient and stable perovskite solar cells.